Analysis of pile group behaviour due to excavtion induced ground movements - Nishanthan, R.; Liyanapathirana, D.S.; Leo, C.J. (Taylor & Francis Group, London, 2013)
This paper presents the impact of excavation induced ground movements on adjacent pile groups. Numerical simulations are performed on free-head and capped piles with different pile configurations. The piles, pile cap and retaining wall are assumed to have linear elastic behaviour. Constitutive behaviour of the soil is modelled using the Mohr Coulomb model. Finite element method was used to model a series of centrifuge tests reported in the literature. The predicted and measured values of deflection and bending moment are compared. The problem was modelled in three dimensions to simulate the arching and shielding effect of piles within the pile group. The response of interior piles and peripheral piles are also investigated. It was found that presence of front piles reduce the detrimental effects on the rear piles within the group. Analysis shows the provision of pile gap significantly reduces the deflection of pile group due to load transfer to the rear piles, which are located away from the excavation wall.